FACTORS RELATED TO NURSES NON-COMPLIANCE IN IMPLEMENTING STANDARD OPERATING PROCEDURES (SOP) IN HEALTHCARE SETTINGS: A SYSTEMATIC REVIEW - Arif Candra; Dodi Wijaya; Anisah Ardiana (UPT Penerbitan Universitas Jember, 2023)
Background: Standard Operating Procedures (SOPs) are an essential aspect of healthcare delivery as they provide guidelines for healthcare providers to ensure consistent quality of care. However, non-compliance with SOPs by nurses is a widespread problem in healthcare settings. Non-compliance can result in serious consequences, such as increased risk of healthcareassociated infections and decreased quality of care. This study aimed to identify the causes of non-compliance among nurses is crucial to developing effective interventions to improve compliance., Methods: A comprehensive search was conducted using electronic databases such as PubMed, Scopus, and CINAHL, using keywords such as